2015
DOI: 10.1016/j.neuroscience.2015.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolic abnormalities during gait with freezing in Parkinson’s disease

Abstract: FoG during a real gait task was associated with impaired frontoparietal cortical activation, as characterized by abnormally low metabolic activity of the premotor area (involved in the indirect locomotor pathway) and abnormally high metabolic activity of the parietal area (reflecting the harmful effect of external cueing).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 127 publications
(189 reference statements)
5
41
1
2
Order By: Relevance
“…As described previously, cortical but not thalamic cholinergic deficits predict reduced executive, attention, and verbal learning scores in PD patients without dementia (Bohnen et al, 2012, 2015), as well as freezing-of-gait symptoms associated with increased demand on and failure of cognitive control and reduced function of cognitive control-associated cortical networks (Bartels & Leenders; 2008; Bohnen et al 2014; Giladi & Hausdorff, 2006; Shine et al, 2013; Tard et al, 2015a,b). In contrast, thalamic cholinergic denervation has been linked to falls, with Bohnen et al noting that compared to other patients, those with a history of falls had an approximately 12% reduction in thalamic AChE activity.…”
Section: 1 Discussionsupporting
confidence: 53%
“…As described previously, cortical but not thalamic cholinergic deficits predict reduced executive, attention, and verbal learning scores in PD patients without dementia (Bohnen et al, 2012, 2015), as well as freezing-of-gait symptoms associated with increased demand on and failure of cognitive control and reduced function of cognitive control-associated cortical networks (Bartels & Leenders; 2008; Bohnen et al 2014; Giladi & Hausdorff, 2006; Shine et al, 2013; Tard et al, 2015a,b). In contrast, thalamic cholinergic denervation has been linked to falls, with Bohnen et al noting that compared to other patients, those with a history of falls had an approximately 12% reduction in thalamic AChE activity.…”
Section: 1 Discussionsupporting
confidence: 53%
“…In contrast to our findings, a previous study in PD with and without FOG showed increased metabolic activity of parietal regions and subcortical nuclei, as well as reduced activity of frontal regions during an upright complex gait task (i.e., combined dual-tasking, passing through a narrow space, and 360°turning) compared with supine rest (36). Notably, participants spent approximately 40% of the time in motor arrest.…”
Section: Discussioncontrasting
confidence: 99%
“…In PD this includes degeneration of cholinergic (Rinne et al, 2008; Karachi et al, 2010; Pienaar et al, 2013), GABAergic and glycinergic cells (Pienaar et al, 2013). Neuroimaging indicates that locomotor deficits in PD patients are associated with additional MLR abnormalities (notably in the PPN), including altered connectivity between the MLR, thalamus, and motor cortical regions (Fling et al, 2013, 2014), abnormal microstructure (Vercruysse et al, 2015; Youn et al, 2015; Wang et al, 2016), atrophy of the MLR gray matter (Snijders et al, 2011; Fioravanti et al, 2015) and abnormal metabolic activity following a walking task (Tard et al, 2015). Additionally, anatomopathological studies revealed the presence in the MLR of alpha-synuclein immuno-reactive Lewy Bodies (e.g., Seidel et al, 2015), and mitochondrial abnormalities (Pienaar et al, 2013) in PD.…”
Section: Possible Role Of the Descending Dopaminergic Pathway In Pdmentioning
confidence: 99%